Comparison of pulsed electric field generation techniques for microbial inactivation application - Jambari, Hanifah (Asian Research Publishing Network (A R P N), 2011)
This paper presents a comparative study on various pulsed electric field (PEF) techniques for liquid food sterilization applications. Pulsed Electric Field (PEF) is an alternative method compared to the conventional food pasteurization method in removing harmful bacteria contained in liquid food products. A Cascaded Multilevel Inverter (CHMI) is proposed as a PEF generator to produce a higher output voltage without using a transformer to inactivate microbial in liquid food. It will reduce the power losses of the system while yielding better sterilization effectiveness as well as reduce cost. The CHMI has been simulated using MATLAB/Simulink software to analyze the performance of the circuit. The simulation results demonstrate that the CHMI can produce both bipolar and unipolar square wave output pulses. This in turn contributes to the flexibility of the CHMI in testing the effectiveness of the PEF produced on liquid food sterilization compared to the conventional method and other power electronics circuits that have been used for similar application.